Indianisation of the Indian Judicial-Legal System - Sudarshan Verma; Abhishek Verma (AG Volumes, 2026)
This chapter seeks to argue for the Indianisation of the judicial system of India. The authors have first tried to define the meaning of the term Indianisation, which briefly means the decolonization of the Indian Judicial System and localising the Justice delivery systems by adapting to the practical realities of our society and thus making it more citizen centric. Further, the authors discussed the need for Indianisation as well as various initiatives like legal reforms, legal language and communication reforms, promoting alternative dispute resolution and cultural sensitivity and lastly, technological integration to meet the desired objective.